Using feral pigeon (Columba livia) to monitor anthropogenic debris in urban areas: a case study in Taiwan’s capital city - Wei-Ting Chen; Wen-Ta Yang; Chia-Ying Ko; Sofia Ya Hsuan Liou; Chia-Hsuan Hsu; Chun-Han Ko; Chung-Hang Hung; Hsiao-Wei Yuan (Scientific Reports)
Abstract The terrestrial environment is a significant source of anthropogenic debris emissions. While most studies on anthropogenic debris focus on the marine environment, our research delves into the effects of human activity on anthropogenic debris ingestion by studying the carcasses of feral pigeons. From January to June 2022, we collected the gastrointestinal tracts (GI tracts) of 46 pigeon carcasses in Taipei, Taiwan’s capital city. The results revealed that 224 anthropogenic debris samples were found, with the dominant form being fibers (71.9%), which are primarily black (29.9%). Fourier transform infrared spectroscopy (FTIR) revealed that the main component of anthropogenic debris is polyethylene (PE) (20.5%), followed by anthropogenic cellulose (19.2%) and various other plastics. This study revealed that the amount of anthropogenic debris and chemical composition in the GI tract significantly increase with increasing human activity. These results prove that feral pigeons are valuable indicators for monitoring anthropogenic debris pollution in urban ecosystems. On the other hand, past research focused on analyzing microplastics, but we confirmed that the GI tract of pigeons has a high proportion of anthropogenic cellulose. Importantly, future studies should consider the potential impacts of anthropogenic cellulose in terrestrial ecosystems, as this could have significant implications for ecosystem health.